Pemasaran Sosial Sebagai Upaya Meningkatkan Praktek Pemberian Asi Esklusif Bagi Ibu Hamil : (Studi Deskriptif Pada Pelaksanaan Program Kelompok Pendukung Ibu Kelurahan Rawa Buaya, Jakarta Barat) - Intani, Amalia Reza; Hati, Getar (Jurnal Ilmu Kesejahteraan Sosial, 2015)
This study aims to explain the social marketing of Mother Support Group Program in Rawa Buaya as the way to improve breast feeding practice for pregnant mothers and to describe the obstacle of the program. The qualitative data were collected by conducting in-depth interview and direct observation. Based on the result of this study, social marketing of Mother Support Group Program has done various social marketing steps and it is one of the way to achieve the change of pregnant mother’s behavior in order to implement breast feeding practice for the further life. This social marketing is implemented with education and participation for community development.